Inequality is Bad for Growth of the Poor (but Not for That of the Rich) - van der Weide, Roy; Milanovic, Branko (Published by Oxford University Press on behalf of the World Bank, 2020)
The paper investigates the relationship between income inequality and future income growth rates of households at different points of the income distribution. The analysis uses micro-census data from U.S. states covering the period from 1960 to 2010, and controls for exposure to imports from China and share of routine jobs, among other variables. It finds evidence that high levels of inequality reduce the income growth of the poor but, if anything, help the growth of the rich.